Poetic Closure in Job: The First Cycle - Seow, C. L. (Journal for the study of the Old Testament, 2010)
Inspired by Barbara Herrnstein Smith’s study of poetic closures, this article considers the artistry of closure in Biblical Hebrew poetry by focusing on a small sample—the seven poems that make up the first cycle of dialogue in Job (Job 3, 4—5, 6—7, 8, 9—10, 11, 12— 14). It is shown that the poems in this sample employ a full range of linguistic, thematic, and structural devices of closure, which, together with other poetic features, enhance the elegance of Joban poetry. It is hoped that this initial foray will encourage other studies of the poetry of closure in the rest of the book of Job, as well as other collections of Hebrew poems.